2012
DOI: 10.1038/pr.2012.193
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis biofilms induce lower complement activation in neonates as compared with adults

Abstract: Background: Staphylococcus epidermidis (se) is an important cause of late-onset sepsis in neonates. se frequently produces a polysaccharide intercellular adhesin (PIa) biofilm, important in the pathogenesis of these infections. Little is known about how the neonatal innate immune system reacts to se biofilm-associated infections. Our hypothesis was that se biofilms induce a lower complement activation in neonates as compared with adults. Methods: cord blood from term infants (n = 15) and blood from adults (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(70 reference statements)
2
4
0
Order By: Relevance
“…Purified PIA from S. epidermidis has previously been identified as modulating complement binding and activation in opsonised human neutrophils (Kristian et al, 2008), whole blood (Fredheim et al, 2011), human serum (Satorius et al, 2013) and neonatal whole blood (Granslo et al, 2013). Our data is consistent and extends these findings demonstrating that PIA may disintegrate from or for a 'bridge' between the bacterial biofilm leukocytes which is consistent with inhibition of opsonisation shown previously (Kristian et al, 2008).…”
Section: Accepted Manuscript Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Purified PIA from S. epidermidis has previously been identified as modulating complement binding and activation in opsonised human neutrophils (Kristian et al, 2008), whole blood (Fredheim et al, 2011), human serum (Satorius et al, 2013) and neonatal whole blood (Granslo et al, 2013). Our data is consistent and extends these findings demonstrating that PIA may disintegrate from or for a 'bridge' between the bacterial biofilm leukocytes which is consistent with inhibition of opsonisation shown previously (Kristian et al, 2008).…”
Section: Accepted Manuscript Discussionsupporting
confidence: 91%
“…More specifically, staphylococcal biofilm matrices have been implicated in complement activation. Here PIA from S. epidermidis has been shown to modulate complement binding and activation in opsonised human neutrophils (Kristian et al, 2008), and induction of complement C5a has been demonstrated in whole blood (Fredheim et al, 2011), human serum (Satorius et al, 2013) and neonatal whole blood (Granslo et al, 2013).…”
Section: ; Stevensmentioning
confidence: 95%
“…Deficiencies in complement factor C3 and IgG are associated with a higher risk of neonatal CoNS-associated sepsis (Lassiter et al, 1991). Furthermore, in a study using an ex-vivo whole-blood sepsis model, S. epidermidis induced significantly lower complement activation in neonatal compared to adult blood (Granslo et al, 2013). This finding suggests that there is a maturational deficiency in the neonatal complement system, which, in part, may explain why neonates are more susceptible to S. epidermidis septic infections than adults.…”
Section: Immunity Against S Epidermidis During Sepsismentioning
confidence: 99%
“…The polysaccharide intercellular adhesin (restricted to a subpopulation of Staphylococci epidermidis ) and the poly-g-DL-glutamic acid (ubiquitous among Staphylococci epidermidis strains) protect the bacteria against cathelicidin and human β -defensin 3 [147, 148]. Moreover, the immaturity of the neonatal complement system impairs the capacity of neonates to fight against biofilm-associated Staphylococci epidermidis infections [149]. Interestingly, a study, dealing with the effects of lactoferrin with antibiotics commonly used in neonatal practice against CoNS, shows a synergic action, demonstrating that lactoferrin may be a promising agent to improve treatments of NS caused by CoNS [150].…”
Section: Neonatal Innate Immune Response Infections and Sepsismentioning
confidence: 99%